The Ballad Matrix Personality, Milieu, and the Oral Tradition - McCarthy, William Bernard (Indiana University Press, 1990)
The Ballad Matrix examines the William Motherwell ballad collection, one of the largest collections of songs gathered during the golden age of ballad collecting in Scotland (1780 to 1830). The collected repertoire of Agnes Lyle of Kilbarchan, Motherwell's most prolific informant, consists of twenty-two full texts, some with tunes, and a number of additional fragments. Revealing how Agnes Lyle relied on the narrative techniques of ballad singing, these songs also show how she achieved expression of personal values and concerns even though her medium, the ballad, was a highly traditional one. When in her ballads Agnes Lyle expressed traditional attitudes toward luxury, sexuality, or death, her expression was uniquely vehement. Furthermore, she was able to express radical social and political attitudes, which are not traditional in balladry. Study of Agnes Lyle's ballads thus allows a better understanding of what it meant for a traditional singer to "learn" a ballad and to what extent she was free to make the song her own.